2021
DOI: 10.1093/ibd/izab256
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Amino Acid Analysis in Newly Diagnosed Pediatric Inflammatory Bowel Disease: A Multicenter Case-Control Study

Abstract: Background Fecal metabolomic profiles differ between pediatric inflammatory bowel disease (IBD) patients and controls and may provide new insights in the pathophysiology of IBD. The role of amino acids, however, is not fully elucidated. We aimed to assess fecal amino acid profiles in pediatric IBD. Methods In this case-control study, treatment-naïve, newly diagnosed pediatric IBD patients and a non-IBD control group, matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Valine belongs to branched chain amino acids, and the increased level in fecal samples was demonstrated to have positive association with the severity of IBD. 15 Arginine was decreased in IBD patients, 14 while mEVs increased its concentration in our results. Arginine, a semi-essential amino acid, is the precursor of nitric oxide (NO) and polyamines, which played a vital role in B-cell maturation, T-cell proliferation, and cytokine production.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Valine belongs to branched chain amino acids, and the increased level in fecal samples was demonstrated to have positive association with the severity of IBD. 15 Arginine was decreased in IBD patients, 14 while mEVs increased its concentration in our results. Arginine, a semi-essential amino acid, is the precursor of nitric oxide (NO) and polyamines, which played a vital role in B-cell maturation, T-cell proliferation, and cytokine production.…”
Section: Discussionsupporting
confidence: 57%
“…13 Previous studies reported that about 17 fecal amino acids were higher in IBD patients compared with healthy individuals. 14,15 In brief, the regulation of lipid and amino acid metabolism is believed to be a promising method to treat IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly higher levels of threonine were found in the fecal metabolites of patients with irritable bowel syndrome (IBD) and ankylosing spondylitis (AS) ( 27 , 48 ). Meanwhile, increased levels of lysine, alanine, and glycine have also been shown to correlate with malabsorption due to intestinal inflammation ( 49 , 50 ). Therefore, the decreased fecal levels of alanine, threonine, aspartate, lysine and glycine could reflect the improved inflammatory status in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the group of children with UC, serum histidine inversely correlated with erythrocyte sedimentation rate (ESR). Histidine fecal levels have been positively associated with more extended disease in UC but not in CD pediatric patients ( Jagt et al, 2021 ). A possible explanation may be either the colonic leakage of histidine and other amino acids or malabsorption.…”
Section: Metabolomics In Ibd and Covid-19mentioning
confidence: 99%